Bowel morbidity following radiochemotherapy and image-guided adaptive brachytherapy for cervical cancer: Physician- and patient reported outcome from the EMBRACE study. Issue 3 (June 2018) - Jensen, Nina Boje Kibsgaard; Pötter, Richard; Kirchheiner, Kathrin; Fokdal, Lars; Lindegaard, Jacob Christian; Kirisits, Christian; Mazeron, Renaud; Mahantshetty, Umesh; Jürgenliemk-Schulz, Ina Maria; Segedin, Barbara; Hoskin, Peter; Tanderup, Kari; et al.
Abstract: Background/Purpose: This study describes late bowel morbidity prospectively assessed in the multi-institutional EMBRACE study on MRI-guided adaptive brachytherapy in locally advanced cervical cancer (LACC). Materials/Methods: A total of 1176 patients were analyzed. Physician reported morbidity (CTCAE v.3.0) and patient reported outcome (PRO) (EORTC QLQ C30/CX24) were assessed at baseline and at regular follow-up. Results: At 3/5 years the actuarial incidence of bowel morbidity grade 3–4 was 5.0%/5.9%, including incidence of stenosis/stricture/fistula of 2.0%/2.6%. Grade 1–2 morbidity was pronounced with prevalence rates of 28–33% during follow-up. Diarrhea and flatulence were most frequently reported, significantly increased after 3 months and remained elevated during follow-up. Incontinence gradually worsened with time. PRO revealed high prevalence rates. Diarrhea ≥"a little" increased from 26% to 37% at baseline to 3 months and remained elevated, difficulty in controlling bowel increased from 11% to 26% at baseline to 3 months gradually worsening with time. Constipation and abdominal cramps improved after treatment. Conclusion: Bowel morbidity reported in this large cohort of LACC patients was limited regarding severe/life-threatening events. Mild-moderate diarrhea, flatulence and incontinence were prevalent after treatment with PROs indicating a considerable and clinically relevant burden. Critical knowledge based on the extent and manifestation pattern of treatment-related morbidity will serve future patient management.